Penggunaan Media Digital Canva dalam Pembelajaran Sosiologi Antropologi Pendidikan untuk Mahasiswa Berkebutuhan Khusus - Nurazizah Rahmi R; Faizal Faizal; Bastiana Bastiana; Rini Lestari; Nur Wulandari (JURNAL ORTO DIDAKTIKA, 2024)
This study evaluates digital learning media created using Canva for the Sociology and Anthropology of Education course. The research involves 101 students and analyzes their perceptions regarding the digital learning media's accessibility, clarity, interactivity, and effectiveness. Using a comprehensive questionnaire, the study examines various aspects of digital learning media, including text readability, color contrast, navigation ease, and overall learning experience. The results indicate overwhelmingly positive responses, with most respondents (over 90%) agreeing that the Canva-based digital learning media enhanced their understanding, motivation, and learning engagement. The research provides insights into the potential of digital learning media in higher education and offers recommendations for future digital learning design.